Determinants of Carbon Emission Disclosure Among Indonesian SOEs: Empirical Evidence from Firm Size and Leverage Dynamics (2021–2024) - Muhammad Rizal Satria (Politeknik Ganesha Medan, 2026)
This study examines the influence of firm size and leverage on carbon emission disclosure among Indonesian State-Owned Enterprises (SOEs) during the period 2021–2024. Using secondary data obtained from sustainability and annual reports, this research adopts a quantitative associative approach with a sample of nineteen SOEs, resulting in seventy-six firm-year observations. Carbon emission disclosure is measured using a comprehensive index based on the Global Reporting Initiative (GRI) 305 Emissions standard, employing a structured content analysis of thirty-seven disclosure items. Multiple linear regression analysis is conducted after fulfilling classical assumption tests, including normality, multicollinearity, and heteroskedasticity diagnostics. The findings indicate that firm size is positively associated with carbon emission disclosure, suggesting that larger enterprises tend to disclose carbon-related information more extensively. In contrast, leverage is negatively associated with disclosure, indicating that firms with higher debt levels are less inclined to engage in voluntary carbon reporting. These results highlight the joint role of organisational scale and financial structure in shaping environmental transparency. To ensure robustness, additional analyses are performed using alternative variable proxies, winsorisation of extreme values, heteroskedasticity-consistent estimators, extended models with control variables, and panel data specifications. The results remain consistent across alternative estimations. This study addresses a gap in the literature by focusing exclusively on State-Owned Enterprises, which operate under heightened public accountability yet remain underexplored in carbon disclosure research. The key novelty lies in demonstrating that financial constraints, reflected through leverage, constitute a more persistent determinant of carbon emission disclosure than organisational size within publicly owned enterprises. This study is subject to limitations related to its SOE-specific focus and reliance on report-based disclosure data, providing avenues for future research in broader ownership and institutional contexts.